2016
DOI: 10.5603/piap.2016.0026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Depression and Anxiety on Asthma-Related Quality of Life

Abstract: Introduction: Asthma is the most prevalent chronic disease in adults. It affects their quality of life. Studies confirm that depression and anxiety occurs in asthma patients. Material and methods:The study involved 96 patients with asthma divided into two groups: patients with controlled (n = 33) and uncontrolled asthma (n = 63). The analysis of asthma control was performed on the basis of the ACT (Asthma Control Test) results. The study used SF-36 (Short Form 36) questionnaire and HADS (Hospital and Depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 16 publications
0
22
0
7
Order By: Relevance
“…the BDI and PHQ-9 scores. Similar relationships between quality of life and depression has been previously reported for different diseases [32][33][34]. Depression and quality of life are both related to general well-being of the patient and emphasise the biopsychosocial aspects of the chronic disease.…”
Section: Discussionmentioning
confidence: 48%
“…the BDI and PHQ-9 scores. Similar relationships between quality of life and depression has been previously reported for different diseases [32][33][34]. Depression and quality of life are both related to general well-being of the patient and emphasise the biopsychosocial aspects of the chronic disease.…”
Section: Discussionmentioning
confidence: 48%
“…We found that a higher proportion of patients who were current smokers were diagnosed with psychological conditions such as anxiety and depression when compared with neversmokers [13]. Psychological disorders such as anxiety and depression in patients with asthma are known to be associated with more severe and uncontrolled asthma and to affect the QoL of these patients [6,70]. Our correlation analysis showed that both anxiety/ depression and smoking independently contribute (although weak correlation) to poor asthma control in patients with severe asthma.…”
Section: Contribution Of Smoking To Asthma Control and Psychological mentioning
confidence: 62%
“…5,6 Ciertamente se conoce que el diagnóstico de ansiedad y depresión en pacientes asmáticos afecta negativamente la calidad de vida. 7,8 Un estudio encontró que los adolescentes con asma tenían un riesgo mayor de desarrollar depresión (2.09 veces más probabilidad) y síntomas de ansiedad (1.83 veces más probabilidad) en comparación con el grupo control. 9 En otro estudio se observó que 44.5 % de los adultos asmáticos cumplía…”
Section: Antecedentesunclassified
“…10 Adicionalmente, algunos estudios han demostrado la presencia de ciertos factores independientes de ansiedad y depresión, que podrían predecir mal control del asma y baja puntuación en el cuestionario de calidad de vida, tabaquismo pasivo, edad avanzada, consumo de drogas, actividad profesional, bajos niveles de educación y ser diagnosticado con asma moderada o grave. 7,11 A pesar de los bajos niveles de control del asma en América Latina, las razones por las cuales este fenómeno ocurre siguen siendo poco conocidas. Por esta razón, nuestro estudio tuvo como objetivo explorar la frecuencia y asociación de la ansiedad y depresión con el control del asma en pacientes ecuatorianos, junto con las implicaciones de las características demográficas y su influencia en nuestros hallazgos.…”
Section: Introductionunclassified